Paralympic judo: Is there evidence for match rigging among athletes with disabilities? - Strielkowski, W.; Shishkin, A. (Annals of Applied Sport Science, 2017)
Objectives. This paper studies the existence or non-existence of match-fixing (or rigging) among judo wrestlers (judoka) with disabilities during the consecutive Paralympic Games from 1988 until 2016. Methods. In our analysis, we use the institutional framework that makes it easy understand and model the incentives of the wrestlers using the readily available data. Our data set consists of official judo matches that took place during the Paralympic Games from Seoul in 1988 to Rio in 2016. We analyze the distribution of wins across judokas, the medal count at the end of each medal tournaments. Results. Our results are quite similar across specifications. There is no significant evidence to prove that some Paralympic judokas tend to be victorious more often on average than it might be expected. Conclusions. We find no evidence can be found to document match rigging in Paralympic judo wrestling. Our analysis does not confirm the corruption story or rule out effort as the explanation. While the incentive structure of promotion leads to gains from trade between wrestlers on the margin for achieving a winning record and their opponents in some other sports with athletes winning a disproportionate share of the matches when they are on the margin, this does not seem to be the case of Paralympic judo. Reciprocity agreements between Paralympic judo teams from different countries are unlikely to exist, suggesting that collusive behavior is carried out solely by individual actors.